Optimasi Media Sosial Instagram @kulinersby dalam Mempromosikan Wisata Kuliner Surabaya - Qorib, Fathul; Widodo, Herru Prasetya; Rinata, Asfira Rachmad (School of Communication - Atma Jaya Catholic University of Indonesia, 2021)
The Instagram @kulinersby social media account is one of the platforms that has been promoting culinary tourism in the city of Surabaya since 2014. This study aims to look at optimizing the @kulinersby Instagram account as one of the culinary tourism promotion media. Several social media marketing concepts are used to see how the optimization works, namely content creation, content sharing, connecting, and community building. All uploads and interactions of followers on the account become primary data sources, then compared with secondary data in interviews with the account manager, namely Syafira Defani Putri. The results of this study indicate that @kulinersby has implemented good management in several aspects, especially for content management, starting from its creation, content sharing such as consistently uploading content and sharing food themes, to connecting with followers through interaction and discussion, as well as collaborating with foodvloggers. Meanwhile, for community building, @kulinersby is still adapting with many communities to be uniform and work well together. This research suggests that @kulinersby owners take full advantage of Instagram by considering various new features and Instagram business insights as evaluation and development material.